The Effectiveness of Supreme Court Regulation No. 5 of 2019 in Efforts to Prevent Child Marriage - Fajri, Muhammad (Jurusan Hukum Acara Peradilan dan Kekeluargaan, 2022)
The birth of Supreme Court Regulation No. 5 of 2019 concerning Guidelines for Trying Marriage Dispensation Applications aims to provide clear rules regarding the procedure for determining or granting marriage dispensation by judges. However, it is considered that it has not made a significant change in the high number of marriage dispensation cases that have entered the judiciary, which at the same time shows the ineffectiveness of limiting the practice of child marriage. The courts that are trying to stem the surge in the practice of child marriage do not seem to have yielded satisfactory results, even with the presence of these guidelines. In reviewing the effectiveness of the law, there are problems with the legal factors themselves, namely the guidelines and Law No. 16 of 2019, which still opens up opportunities for the practice of child marriage for urgent reasons that are still multi-interpreted. Apart from that, on societal factors, the low level of public understanding of the dangers of child marriage can be seen from the rise of permissive free association, and on cultural factors, there are still members of the public who practice child marriage for reasons justified by their culture.